Pola Pertumbuhan Lactobacillus sp. F213 Selama Fermentasi Pada Sari Buah Terung Belanda (Solanum betaceum Cav.) - Wya Saraswati, Puspasecca; Nocianitri, Komang Ayu; Hapsari Arihantana, Ni Made Indri (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 10 No 4 (2021): Jurnal ITEPADO - 10.24843/itepa.2021.v10.i04.p08, 2021)
The objective of this research was to determine the growth pattern of Lactobacillus sp. F213 during fermentation in tamarillo juice (Solanum betaceum Cav.) and to obtain the fermentation time that showed optimal growth. This research used a Completely Randomized Design with fermentation time (0 hours, 4 hours, 8 hours, 12 hours, 16 hours, 20 hours, 24 hours, 28 hours and 32 hours) as a treatment. Each treatment was repeated 2 times to obtain 18 experimental units. Variable observed were total LAB, total sugar, total acid and pH. The data results were analysed with quantitative descriptive methods The results of this study indicated that the growth pattern of Lactobacillus sp. F213 in tamarillo juice during fermentation in 0–4 hours was in the lag phase, fermentation time of 8-12 hours was in an exponential growth phase or log phase, fermentation time of 16–20 hours was in the stationary phase and at the fermentation time of 24–32 hours was in the death phase. The optimal growth was obtained at 20 hours of fermentation time with a total value of LAB 9,08 Log CFU/ml.